Shari’a compliance by Malaysian Muslim businesses with respect to guidelines given in Islamic marketing - Sayyed Ahmad, Mohd. Ismail; Wan Jusoh, Wan Jamaliah; Wan Husain , Wan Rohaida (IISTE, 2014)

(untitled)
This research aims to investigate the perceptions of Muslim businessman regarding the extent to which Malaysian businesses comply with the Shari’a rules and regulations given in Islamic Marketing Information on perceptions of Muslim businessman were obtained by administering a structured survey questionnaire, by trained enumerators, in various States of Peninsular Malaysia. A total of 150 completed questionnaires were used in the research analysis. The components of the questionnaire were statements derived from the Quran and the Sunnah, and also those reported in the Islamic literature. The findings from this research indicate that businesses generally felt that for most of the statements presented to them on Islamic marketing, only up to 50% of business respondents adhered to Islamic Marketing guidelines. These were some differences though. The responses were more positive with respect to Halal products, in which a higher percentage of businesses were perceived to follow this Islamic guideline.